Analisis Pengaruh Parallax Scrolling Pada Situs Web Terhadap User Experience - Maulani Camaliah Maramida; Ismiarta Aknuranda; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
User Experience (UX) is an important aspect in the development of digital business as it is one of the key in website content. Researchers have attributed a pleasurable user experience to the fulfillment of the following variables: usability, satisfaction, enjoyment, fun and visual appeal. Parallax scrolling as one of the web design techniques is considered to bring UX to a new interactive level and is even considered a new limitation in UX. Therefore, parallax scrolling has recently become quite popular among web developers. Parallax scrolling is a visual effect that duplicates the depth of an image or two-dimensional screen to make it look three dimensional. Unfortunately, speculation about parallax scrolling and UX relationships is still emerging because parallax scrolling is considered bad for search engine optimization (SEO), weakening internal linking and causing load duration due to the large number of images used in websites with parallax scrolling which may then potentially have an effect on UX. In this study used the above variables in order to see how the user experience when interacting with the website with and without parallax scrolling and find the reason why parallax scrolling is considered to have an effect or no effect on UX.The results showed that participants' experience did not differ greatly, so parallax scrolling concluded did not significantly affect UX. Another reason why parallax scrolling is considered to be unaffected is that in the study only two participants were aware of the effects of parallax scrolling on the website they were using, so it was not certain that the assessment by all participants was due to the use of parallax scrolling.